Neo-sex chromosomes and adaptive potential in tortricid pests - Sýkorová, Miroslava (Jihočeská univerzita, 2015)
Although most of moths and butterflies possess high number of small undifferentiated chromosomes, in the family Tortricidae extraordinary large Z chromosome has been observed. In this study, the physical mapping of this sex chromosome in the major pome fruit pest Cydia pomonella (Tortricidae) revealed a fusion between an ancestral Z chromosome and chromosome 15 in Bombyx mori reference genome. Furthermore, the sex linkage analysis by qPCR has shown that the rearrangement originated in common ancestor of tortricid subfamilies Olethreutinae and Tortricinae. As the Bombyx mori chromosome 15 contains several genes involved in detoxification pathways and insecticide resistance, this fusion could have facilitated adaptive evolution and radiation of tortricid pests.
Neo-sex chromosomes and adaptive potential in tortricid pests
Keywords: pohlavní chromosomy; obaleč jablečný; adaptivní evoluce; chromosomální fúze; resistence k insekticidům; BAC-FISH; qPCR; sex chromosomes; codling moth; adaptive evolution; chromosomal fusion; insecticide resitance; BAC-FISH; qPCR